North-Temperate and Boreal annual median TP concentrations and seasonal climate means from 389 lakes, 1998-2017 - Peter Isles; Irena Creed; Dag Hessen; Pirkko Kortelainen; Michael Paterson; Francesco Pomati; James Rusak; Jussi Vuorenmaa; Ann-Kristin Bergström (Environmental Data Initiative, 2023)
This dataset accompanies a paper submitted for publication to Limnology and Oceanography Letters, expected publication year 2023, by Isles et al., entitled "Widespread synchrony in phosphorus concentrations in northern lakes linked to winter temperature and summer precipitation." This dataset comprises April-November median TP concentrations for 389 lakes in Fennoscandia, the north-central and northeastern USA, and central to eastern Canada, between 1998 and. 2017. The dataset also includes seasonal means for climate variables divided into winter (DJF), spring (MAM), summer (JJA), and fall (SON) means of air temperature, wind speed, and precipitation. The data all originate with publicly collected datasets, and many data source have data from additional time periods or for additional variables collected over longer time periods available from websites or through contact forms.